Novel Single Nucleotide Polymorphisms of Lysozyme (C-Type) Gene in Donkey (Equus Asinus) Populations in Marmara Province of Turkey - Raziye Işık (Turkish Journal of Agriculture: Food Science and Technology)
The major antimicrobial proteins in donkey milk are lysozyme, lactoferrin, lactoperoxidase and immunoglobulins. Lysozyme has an important role in the host defense by way it inhibits the pathogenic bacteria. The aim of this study is to investigate the Lysozyme (LYZ) gene polymorphism in 82 donkeys reared in Thrace region of Turkey. 716 bp long partial 5’ UTR, exon 1, intron 1, exon 2 regions of LYZ gene were amplified and PCR products were analyzed via DNA sequencing. Three novel single nucleotide polymorphisms (SNPs) were identified as g.1782775A>G, g.1782924A>G and g.1782960T>C in the first intron of LYZ gene. The partial DNA sequence of LYZ gene in donkeys was reported in the present study and sequences of LYZ were entered to NCBI Genbank database with the accession number: MK984689-MK984692. This SNP may have an effect on immune system and milk traits in donkeys and additional studies are needed to confirm this assumption for donkey breeding.